Personal Development and Soft Skills for Teachers - Singh, Meenakshi (JOURNAL OF INDIAN EDUCATION, 2012)
Teaching is a profession and teacher education is a process of professional preparation of teachers (NCFTE 2009, p.15). One of the main functions of a teachers’ training college is to produce teachers who are skilled in communication and present the updated subject matter in a manner that is interesting and easy to understand. At various forums people raise an opinion that the teacher education curricula lack training in development of the soft skills which are most essential for this profession. The training in interpersonal communication skills and language proficiency is found wanting. The NCF 2005 reiterates that ‘the existing teacher education programmes do not recognise the centrality of language in the curriculum’. (NCF, 2005) School teachers continue to be isolated from centres of higher learning and their professional development needs remain unaddressed. (Batra, 2005). During an exercise on syllabus reforms at the Faculty of Education, Banaras Hindu University, this problem was realised, and an audit course of 1 credit on ‘Personal Development and Soft Skills for Teachers’ was proposed. This paper presents a detailed account of this exercise on two groups of 40 students each in two consecutive semesters of the 2010- 2011 batch of Bachelor of Education. The designing of the programme, its conduction over fifteen classes of one and a half hour duration, the modalities of interaction and training, and the evaluation as well as the outcome of the entire endeavour is presented in this paper.